Opt-in e-mail marketing influence on consumer behaviour: A Stimuli–Organism–Response (S–O–R) theory perspective - Neo Ligaraba; Tinashe Chuchu; Brighton Nyagadza (Cogent Business & Management, 2023)
The paper examines the influence of opt-in e-mail marketing on consumer behaviour. The study attempts to extend the Stimuli-Organism-Response (S-O-R) theory that has been broadly explored in consumer research. Following a critical review of the literature organisation approach, a hypothetical model has been proposed for this study, based on identified factors, such as, informational value, entertainment-based message content, layout, visual appeal, attitude toward e-mail advertising and intention towards the sender in the context of opt-in email marketing. Data were collected in South Africa through an online survey of 436 opt-in e-mail marketing subscribers. Structural equation modelling (SEM) was employed to measure the proposed hypotheses of the study. The research results suggest that even during a pandemic, e-mail marketers could employ certain features in promotional and informational e-mail marketing communication, particularly informational value, entertainment-based message content, layout, visual appeal, as a means to design their e-mail marketing messages and plan e-mail advertising campaigns. The findings of the study are intended to advance the e-mail marketing knowledge base to help marketers during a pandemic, such as COVID-19. The paper provides marketers with relevant insights on how to effectively engage with e-mail subscribers.
Keywords: 650; COVID-19 pandemic; Consumer behaviour; South Africa; e-mail marketing; opt-in e-mail marketing; subscribers